766 NON-INVASIVE ASSESSMENT OF RIGHT VENTRICLE TO ARTERIAL COUPLING FOR PROGNOSIS STRATIFICATION OF FIBROTIC INTERSTITIAL LUNG DISEASE. (15th December 2022) - Buongiorno, Federica; Buonauro, Agostino; Canora, Angelo; Canonico, Mario Enrico; Esposito, Roberta; Sanduzzi, Alessandro; Bocchino, Marialuisa; Esposito, Giovanni; Santoro, Ciro
Abstract: Background: The coupling of the right ventricle (RV) to the pulmonary circulation is an indicator of RV performance non-invasively estimable by echocardiography. There are no data about its use in patients affected by fibrotic interstitial lung diseases (f-ILD). Methods: Fifty f-ILD patients, including 27 cases with idiopathic pulmonary fibrosis (IPF), (M=37; mean age 67±7 yrs) were studied with standard and speckle tracking echocardiography and compared to 30 age-matched healthy volunteers. Mean patients follow-up was of 70±4 months. Results: Fibrotic-ILD patients had a larger right ventricle (RV) and a worst diastolic function as RV-global longitudinal strain (GLS) was significantly lower along with higher systolic pulmonary artery pressure (sPAP) estimates in comparison with controls. Conversely, tricuspid annular systolic excursion (TAPSE) did not differ between controls and patients. Median values of TAPSE/sPAP and RV-GLS/sPAP were significantly reduced in f-ILDs patients (p<0.0001). Patients with a RV-GLS/sPAP below the median value had a shorter survival (61 vs. 74 months, p=0.01), this parameter being an independent predictor of worse outcome. Conclusion: Low estimates of RV-GLS/sPAP are predictive of worse outcome in f-ILD patients. RV coupling seems to be a promising surrogate biomarker of RV performance to discriminate the patient phenotype with significant management and prognosis repercussions. Figure. Kaplan-Meier curves representative of the cumulative survival of idiopathic pulmonary fibrosis (IPF) patients vs. those with fibrotic-interstitial lung diseases other than IPF (here reported as noIPF). B) Kaplan-Meier curves representative of the cumulative survival of the whole study population according to the right ventricle (RV) coupling to the pulmonary circulation, estimated as the ratio between the RV-global longitudinal strain (RV-GLS) and the systolic pulmonary artery pressure (sPAP).